What does Lawfare mean in Latin America? A new framework for understanding the criminalization of progressive political leaders - Vegh Weis, Valeria (Punishment & society, 2023)
This article addresses the origins of the term lawfare, as well as different definitions developed in the Global North and the Global South while proposing a conceptualization linked to the particularities of this socio-legal phenomenon in Latin America. Focusing on the cases of Brazil and Argentina the article deploys the notions of phycological, judicial and media warfare to analyze the different dimensions that an analysis of lawfare opens in relation to democracy, the penal system, and mainstream media. The article also explores different dimensions of lawfare and a notion in Spanish with the potential to replace the anglicism: dripping coup (golpe por goteo). Finally, the article proposes different measures to counteract lawfare in the judicial, educational, media, and social spheres. In particular, the conclusions refer to the relevance of social movements in what can be conceptualized as a “cautionary popular criminology”.